2005
DOI: 10.1080/00365520410009348
|View full text |Cite
|
Sign up to set email alerts
|

Responses of anal constipation to biofeedback treatment

Abstract: Even in the presence of negative predictors, biofeedback is a valuable treatment option in a substantial proportion of constipated patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 27 publications
1
21
0
2
Order By: Relevance
“…However, there were no significant differences between responders and non-responders in the current study and several reports are in agreement with our findings (15, 25). …”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…However, there were no significant differences between responders and non-responders in the current study and several reports are in agreement with our findings (15, 25). …”
Section: Discussionsupporting
confidence: 94%
“…The results showed that the inability to evacuate an intrarectal balloon on the balloon expulsion test was related to the failure of biofeedback therapy. Several previously published studies using various expulsion tests have also demonstrated that impaired expulsion capacity is related to poor treatment outcomes (24, 25). The reason for these results is unclear; however, because the severity of defecatory dysfunction was evaluated by means of the balloon expulsion test (25), we speculate that severe defecatory dysfunction prior to biofeedback therapy is related to treatment failure.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Physiotherapy or biofeedback is the next step in both patients with or without slow transit or anismus [9,10] . In patients with constipation, RCI is also used to clean the bowel.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, this test should be integrated along with other anorectal physiologic tests. Some studies reported a capability of BET for predicting the outcomes in patients following biofeedback therapy [12][13][14] and further studies are necessary regarding this issue.…”
Section: 11mentioning
confidence: 99%